2019
DOI: 10.1002/alr.22410
|View full text |Cite
|
Sign up to set email alerts
|

Diverse phenotypes and endotypes of fungus balls caused by mixed bacterial colonization in chronic rhinosinusitis

Abstract: Background:The pathogenic roles of fungus and bacteria in chronic rhinosinusitis (CRS) remain unclear. Recently, we described the bacterial ball, which is distinct from the fungus ball, as an unusual phenotype of bacterial infection. In this study, we investigated the clinical, histopathologic, and immunologic characteristics of sinonasal microorganic materials, including fungus ball and bacterial ball. Methods:In this study, we enrolled 80 CRS patients with sinonasal microorganic materials and 10 control subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
12
1
Order By: Relevance
“…Contrary to our expectations, fungi exhibit very complex behaviors [6]. Recently, Kim et al [7] reported that fungus balls are a subtype of bioballs, which consist of four phenotypes (fungus ball, bacterial ball, mixed ball, and double ball) [7]. These types appear similar; therefore, it is not possible to discriminate them during endoscopic sinus surgery.…”
contrasting
confidence: 60%
“…Contrary to our expectations, fungi exhibit very complex behaviors [6]. Recently, Kim et al [7] reported that fungus balls are a subtype of bioballs, which consist of four phenotypes (fungus ball, bacterial ball, mixed ball, and double ball) [7]. These types appear similar; therefore, it is not possible to discriminate them during endoscopic sinus surgery.…”
contrasting
confidence: 60%
“…The most commonly involved fungal agents are Aspergillus species, but many other species of fungi are also reported 1,14,15 . Nevertheless, the pathogenic role of fungal organisms and bacterial colonies, but also their complex interactions in CRS remain unclear 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of early work looking at S100A7, also called psoriasin, focused on psoriasis [ 96 , 97 ]. However, several studies suggest that S100A7 may have a role in several respiratory diseases, including lung cancer [ 98 ], asthma [ 99 ], rhinosinusitis [ 100 ], pulmonary complications of systemic sclerosis [ 101 ], and bacterial exacerbations [ 102 ]. S100A7 is a chemotactic protein for CD4+ T cells and neutrophils present in the skin epidermis [ 103 ].…”
Section: Linking S100 Proteins To Pulmonary Disease Outcomesmentioning
confidence: 99%
“…It also functions as a direct bactericidal protein [ 104 ]. Kim et al demonstrated that levels of S100A7 and S100A8/A9 were reduced in chronic rhinosinusitis (CRS) patients with a mixed ball of bacteria and fungi compared to a fungal ball [ 100 ]. This implies that the barrier function of the nasal epithelial cells is reduced in mixed fungal and bacterial infections thus putting patients at risk of developing an invasive fungal infection.…”
Section: Linking S100 Proteins To Pulmonary Disease Outcomesmentioning
confidence: 99%